Analysis of the Water Soluble Extract of Comedones - Hernandez, Leopoldo G; Puhvel, S Madli (Journal of investigative dermatology, 1978)
The water soluble fraction of 713 open comedones, pooled from both the face and back of 47 subjects representing all grades of acne, were analyzed for total protein content, carbohydrate content, and for identification of specific proteins. In the water soluble fraction, the protein content represented 11.5%, and carbohydrate content 0.2% of the total comedonal crude weight. Esterase and hyaluronidase activity was demonstrated. Propionibacterium acnes antigenic material, serum albumin, and serum Zn alpha 2 glycoprotein, a minor serum constituent, were identified by immunodiffusion and immunoelectrophoresis.